Medan as a Multicultural City: Ethnic and Cultural Dynamics in the Late 19th Century - Sartika Sari Situmorang; Mawar Situmorang; Lisbet Cintani Lumban Gaol; Elizabeth Novita Pakpahan; Lister Eva Simangunsong (Warisan: Journal of History and Cultural Heritage, 2025)
This study investigates the multicultural character of Medan in the late 19th century, with a focus on the intricate ethnic and cultural dynamics that influenced the city’s evolution during the colonial era. As a rapidly growing urban hub in East Sumatra, Medan attracted a diverse array of migrant communities—including Malays, Bataks, Chinese, Indians, and Europeans—each of which played a role in shaping the city’s socio-cultural landscape. This research addresses the question of how these ethnic groups interacted, negotiated spatial boundaries, and coexisted within the colonial urban order. Using a qualitative historical approach, the study draws upon archival materials, colonial administrative records, and travel writings to reconstruct interethnic relations and patterns of cultural exchange. The findings suggest that Medan’s multiculturalism was not simply a consequence of demographic plurality, but was deeply embedded in colonial economic imperatives, labor migration systems, and spatial planning strategies that regulated intergroup contact. Ethnic enclaves emerged as both sites of cultural preservation and zones of contestation, giving rise to hybrid identities and practices. The study concludes that 19th-century Medan offers a formative example of colonial urban multiculturalism—shaped by global migration and colonial governance—and provides valuable historical insight into the roots of ethnic pluralism in contemporary Indonesia.